2013
DOI: 10.1080/17451000.2013.810755
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of salmon lice in the Hardangerfjord

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Versions of published Taylor & Francis and Routledge Open articles and Taylor & Francis and Routledge Open Select articles posted to institutional or subject repositories or any other third-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 22 publications
5
103
0
Order By: Relevance
“…), while the inner fjord branches were dominated by small-sized species like Microsetella and Oithona. A similar pattern was found by previous studies in Hardangerfjord (Gundersen 1953;Lie 1967), indicating a frequent exchange between the fjord and coastal waters (Asplin et al 2014). The along-fjord trend in the zooplankton composition was also reflected in the diet of sprat, but the variability among stations was pronounced.…”
Section: Spatial and Interannual Variation In Diet Compositionsupporting
confidence: 72%
“…), while the inner fjord branches were dominated by small-sized species like Microsetella and Oithona. A similar pattern was found by previous studies in Hardangerfjord (Gundersen 1953;Lie 1967), indicating a frequent exchange between the fjord and coastal waters (Asplin et al 2014). The along-fjord trend in the zooplankton composition was also reflected in the diet of sprat, but the variability among stations was pronounced.…”
Section: Spatial and Interannual Variation In Diet Compositionsupporting
confidence: 72%
“…On seasonal timescales, salinity drives stratification during spring-summer and the water column is more homogenous during winter. Additionally, Asplin et al (2014) reported regular episodes of water exchange between Hardangerfjord and the NCC that homogenized the upper 50 m of the fjord by mixing with coastal water. During these events the water temperature inside the Hardangerfjord regularly becomes identical with that of the adjacent coastal North Sea (Asplin et al, 2014).…”
Section: The Study Areamentioning
confidence: 99%
“…The bathymetry and hydrographic conditions of the fjords have been described elsewhere (Helle, 1978;Mathew and Sands, 1973;Bakke and Sands, 1977;Erga and Heimdal, 1984;Asplin et al, 2014). In the following only a brief account, based on the above studies, is given.…”
Section: The Study Areamentioning
confidence: 99%
“…For marine animals that develop in the water column, larval stage duration determines the length of time that larvae are subject to transport by currents and exposed to sources of mortality (O'Connor et al 2007;Treml et al 2008). Therefore, predicting disease transmission of marine pathogens requires a considerable understanding of the biology of the agent and its interaction with the surrounding physical environment (Murray 2009;Asplin et al 2014;Johnsen et al 2014).…”
Section: Introductionmentioning
confidence: 99%